Analysis of land use and cover and its relationship with fire in the indigenous lands of the municipality of Amarante, Maranhão, Brazil - Fernandes, Helen Giovanna Pereira (2024)
The state of Maranhão has high rates of deforestation and fires, especially in the south and southeast, where the Cerrado and Amazon biomes are present. In this context, the municipality of Amarante stands out, located in the southern region of the state, which is home to the second largest cattle herd in the state and plays a significant role as an agricultural hub. The municipality is also part of the MATOPIBA Economic Frontier. The aim of this study is to analyze land use and cover and its relationship with fire in the Indigenous Lands of the Municipality of Amarante, Maranhão, Brazil. Using remote sensing techniques and geospatial data analysis, the aim is to investigate the patterns of deforestation, forest fragmentation and the occurrence of fires in these indigenous lands. Through a temporal approach, analyzing the period from 1985 to 2020 with 5-year intervals between each cut, results were obtained that reveal a direct correlation between the advance of agricultural activities, the frequency of fires, deforestation and illegal logging in the region. The study also highlights the increase in violence and territorial conflicts resulting from the expansion of these economic activities, directly affecting indigenous populations and highlighting the territorial tension related to land use and coverage. These findings highlight the urgent need to implement conservation and sustainable land use management strategies in indigenous areas, with a view to protecting biodiversity and traditional ways of life.